TG-FTIR Study of Degradation Mechanism and Pyrolysis Products of High Molecular Polyacrylonitrile with Different Oxidation Degree - Zhang, Li; Liu, Zhiling; Dai, Yongqiang; Jin, Riguang (Asian Journal of Chemistry, 2013)
Thermal degradation of both high molecular polyacrylonitrile precursor fiber and pre-oxidation fibers with different extent of stabilization were studied in N2 atmospheres using thermogravimetric analysis coupled with Fourier transform Infrared analysis (TG-FTIR). Degradation mechanism and volatile products at various temperatures of each sample were studied. The results show that the fibers with higher stabilization were more stable. It is indicated that degradation process of fibers can be divided into three stages and most of the weight loss occurs at the second stage. The gaseous products such as H2O, NH3, HCN, CO and CO2 are formed, meanwhile, the amount of volatile products of fibers were closely related to stabilization of fibers.